2010
DOI: 10.1158/1078-0432.ccr-10-0891
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling Reveals Alternative Genetic Pathways of Meningioma Malignant Progression Dependent on the UnderlyingNF2Status

Abstract: Purpose: Meningiomas are the most common central nervous system tumors in the population of age 35 and older. WHO defines three grades predictive of the risk of recurrence. Clinical data supporting histologic malignant progression of meningiomas are sparse and underlying molecular mechanisms are not clearly depicted.Experimental Design: We identified genetic alterations associated with histologic progression of 36 paired meningioma samples in 18 patients using 500K SNP genotyping arrays and NF2 gene sequencing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 40 publications
(37 reference statements)
4
79
0
Order By: Relevance
“…34,38,39,62,78 In addition to dysregulation of specific signaling pathways, NF2-mutated meningiomas may also exhibit greater chromosomal instability than NF2-wild type counterparts. 32 However, no targetable dependency in the NF2 pathway currently exists.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…34,38,39,62,78 In addition to dysregulation of specific signaling pathways, NF2-mutated meningiomas may also exhibit greater chromosomal instability than NF2-wild type counterparts. 32 However, no targetable dependency in the NF2 pathway currently exists.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…7-12 A recent genomic study demonstrated that there were two main pathways of progression in meningiomas: one linked to bi-allelic NF2 loss and genomic instability, and the other characterized by the absence of chromosome imbalances. 13 As the mechanism underlying NF2-related genomic instability is…”
Section: Introductionmentioning
confidence: 99%
“…While SNP arrays have been used in the characterization of many types of tumors, to the best of our knowledge, few studies have been reported so far in which they have been applied to analyze large series of meningiomas. In fact, until now only 100K SNP arrays have been used to characterize an atypical meningioma (Krupp et al, 2008) and 18 meningiomas have been studied with 500K arrays (Goutagny et al, 2010).…”
Section: Introductionmentioning
confidence: 99%